Effects of electromagnetic pulse exposure on gelatinase of blood–brain barrier in vitro. (2nd January 2017) - Zhou, Yan; Qiu, Lian-Bo; An, Guang-Zhou; Zhou, Jia-Xing; Du, Le; Ma, Ya-Hong; Guo, Guo-Zhen; Ding, Gui-Rong
ABSTRACT: The biological effects of electromagnetic pulse (EMP) on the brain have been focused on for years. It was reported that gelatinase played an important role in maintaining brain function through regulating permeability in the blood–brain barrier (BBB). To investigate the effects of EMP on gelatinase of BBB, an in vitro BBB model was established using primary cultured rat brain microvascular endothelial cells (BMVEC), astrocytes and half-contact culture of these cells in a transwell chamber. Cultured supernatant and cells were collected at different time points after exposure to EMP (peak intensity 400 kV/m, rise time 10 ns, pulse width 350 ns, 0.5 pps and 200 pulses). Protein levels of cellular gelatinase MMP-2 and MMP-9, and endogenous inhibitor TIMP-1 and TIMP-2 were detected by Western blot. The activity of gelatinase in culture supernatant was detected by gelatin zymography. It was found that compared with the sham-exposed group, the protein level of MMP-2 was significantly increased at 6 h ( p < 0.05), and the protein level of its endogenous inhibitor TIMP-2 did not change after EMP exposure. In addition, the protein levels of MMP-9 and its endogenous inhibitor TIMP-1 did not change after EMP exposure. Gelatin zymography results showed that the activity of MMP-2 in the inner pool and the outer pool of the transwell chamber was significantly increased at 6 h after EMP exposure compared with that of the sham group. These results suggested that EMP exposure could affect the expression and activity of MMP-2 in the BBB model.